Analisis Terhadap Implementasi Peraturan Perundang-Undangan Di Indonesia Sebagai Upaya Meningkatkan Kesejahteraan Masyarakat - Aprita, Serlika (BULETIN ADALAH, 2021)
In the application of laws and regulations in Indonesia, there are many weaknesses, one of which does not meet the concept of fair efficiency as regulated in Law Number 12 of 2011 concerning the Establishment of Legislations, both at the level of formation, application or law enforcement. Today, technology is experiencing an increasingly rapid development along with the times. The development of technology is something that cannot be touched. The role of law as a tool of social control involves the state to run it, therefore the role of the executive and legislature in making the rule of law is very important and dominant because the state has the obligation to protect all its citizens.